Civil Law Analysis of the Blood Supply Cooperation Agreement between PMI Seluma and RSUD Tais - Ahmad Ali Widodo; Hangabei, Sinung Mufti; Putra, Hendi Sastra; Ardinata, Mikho (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
Blood availability plays a strategic role in health services because it directly affects patient safety and the continuity of medical treatment. In Seluma Regency, the collaboration between the Indonesian Red Cross (PMI) and Tais Regional General Hospital (RSUD) is outlined in a Memorandum of Understanding (MoU) to ensure a safe, adequate, and timely blood supply. However, its implementation still faces various obstacles, such as limited stock and delays in distribution, which have the potential to disrupt health services and patient rights. This study aims to analyze the implementation of the MoU from a civil law perspective, focusing on the validity of the agreement, the fulfillment of the rights and obligations of the parties, and the dispute resolution mechanism. The method used is normative legal research supported by empirical data through a review of the Civil Code, contract theory, and field findings. The results of the study show that the MoU has met the requirements for a valid agreement according to Articles 1320 and 1338 of the Civil Code, but there are still weaknesses in the implementation of the contract that have the potential to cause default, thus requiring the strengthening of regulations and supervision of cooperation.